Voice and Discourse in the Irish Context (Springer International Publishing, 2018)
This book examines the intersection of culture and language in Ireland and Irish contexts. The editors take an interdisciplinary approach, exploring the ways in which culture, identity and meaning-making are constructed and performed through a variety of voices and discourses. This edited collection analyses the work of well-known Irish authors such as Beckett, Joyce and G. B. Shaw, combining new methodologies with more traditional approaches to the study of literary discourse and style. Over the course of the volume, the contributors also discuss how Irish voices are received in translation, and how marginal voices are portrayed in the Irish mediascape. This dynamic book brings together a multitude of contrasting perspectives, and is sure to appeal to students and scholars of Irish literature, migration studies, discourse analysis, traductology and dialectology.